NONLINEAR VARIATIONAL INCLUSIONS INVOLVING (A, η) MONOTONE MAPPINGS IN HILBERT SPACES - Ram, T.; Iqbal, M. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2025)
In this work, we consider the nonlinear variational inclusion problem (NVIP) in real Hilbert spaces, which involves (A, η)-monotone mappings. We propose an iterative algorithm for finding the approximate solution to (NVIP) by using the resolvent operator technique, and we also explore the convergence criteria of the sequence generated by the resolvent iterative algorithm under some appropriate conditions.